Ultraviolet-aging-resistant high-strength high-modulus PBO fiber and preparation method thereof
By adopting batch prepolymerization and final polymerization process in the preparation process of PBO fibers, combined with anti-ultraviolet agent UV326 and densification treatment, the problem of aging of PBO fibers under ultraviolet light is solved, and fiber preparation with high strength, high modulus and good UV resistance is achieved.
Patent Information
- Application Number
- CN202311137874.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-07
AI Technical Summary
Polyptyrenol benzodioxazole (PBO) fibers age rapidly under ultraviolet light and their mechanical properties decrease, limiting their application.
The batch prepolymerization process and the final pooling process are adopted, and the reaction temperature and time are controlled through equipment such as coaxial ribbon stirrer and twin screw extruder, and the anti-ultraviolet agent UV326 is added, and the fibers are improved by densification treatment.
The high strength and high modulus of PBO fibers and good anti-ultraviolet aging performance are achieved, and the strength retention rate reaches 62.5%-90.5%, which significantly extends the service life of the fiber.
Smart Images

Figure CN119571492A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of high-performance fiber preparation, and in particular to a high-strength and high-modulus PBO fiber resistant to ultraviolet aging and a preparation method thereof. Background Art
[0002] Poly(p-phenylene benzobisoxazole) (PBO) fiber is a high-performance organic fiber with high thermal stability, high molecular orientation and chain rigidity. It is a member of the heterocyclic aromatic polymer family with a rigid rod-like structure.
[0003] PBO fiber has excellent mechanical properties, with strength and modulus up to twice that of Kevlar fiber. This property depends on the conjugated polymer main chain between benzobisoxazole and benzene ring. This structure will produce π electron delocalization and resonance effect, thereby stabilizing the PBO structure.
[0004] PBO fiber spinning adopts dry-jet wet spinning technology. During this process, the molecular chain of PBO is highly oriented along the fiber axis, and the tension applied to the fiber axis gives it high crystallinity and orientation. The conjugated aromatic heterocyclic structure on the PBO molecular chain and the solid phase carbide after heat treatment make the fiber have excellent heat resistance and flame retardancy. Its thermal decomposition temperature is as high as 650°C in a nitrogen atmosphere, and it can be used for a long time at 300°C. The limiting oxygen index (LOI) of PBO fiber is 68, so it can be widely used in aerospace, fire protection and bulletproof fields.
[0005] Even with such excellent performance, PBO fiber still has a fatal flaw in its application. Under ultraviolet light, the aging process of PBO fiber is rapid, and the mechanical properties drop sharply, making it lose its practical value, which greatly limits the application of PBO fiber. Poly(p-phenylene benzobisoxazole) (PBO) fiber has high strength, modulus, high temperature resistance and good flame retardant properties. It is the organic fiber with the best comprehensive performance at present. However, PBO fiber has its fatal flaw, that is, its anti-ultraviolet aging performance is relatively weak. Therefore, the research on the anti-ultraviolet aging performance of PBO fiber has always attracted much attention.
[0006] At present, related research mainly focuses on the surface modification of inorganic nanoparticles and the blending of ultraviolet absorbers, stabilizers and PBO polymer solutions. The ultraviolet resistance is not stable enough. With the extension of the use time, the ultraviolet absorbers and other substances in PBO are gradually lost, and its ultraviolet resistance will also decrease. In recent years, the in-situ copolymerization method to improve the ultraviolet resistance of PBO fibers has gradually been recognized by researchers.
[0007] CN201110257597.4 discloses a method for anti-ultraviolet light aging of poly(p-phenylene benzobisoxazole) fiber, wherein ethanol is added dropwise to a mixed solution of a coupling agent and an acidic medium, and stirred to obtain solution A; after a promoter is dissolved in deionized water, ethanol is added dropwise, stirred, a precipitant is added, and then an acidic medium is added dropwise to dissolve all the precipitates, to obtain solution B; solution A is added dropwise to solution B, stirred, polyethylene glycol is added dropwise, the temperature is raised, and PBO fiber is immersed in the solution under the assistance of ultrasonic oscillation, dried, and a uniform anti-ultraviolet light aging gel coating of 0.02 to 0.05 mm is formed on the surface of the PBO fiber. The internal structure of PBO is not changed, but irreversible damage to the fiber body is inevitable during the modification process, resulting in reduced fiber strength, and the cost is high and industrialization is difficult.
[0008] CN201010270180.7 discloses a method for preparing polyphenylene benzobisoxazole fiber resistant to ultraviolet aging, which comprises adding raw materials according to a proportion into a prepolymerization kettle, removing hydrogen chloride gas at a certain temperature, gradually heating to 160-180°C, reacting for 12-48 hours, transferring to a twin-screw reactor for post-polymerization, obtaining a PBO / PPA spinning stock solution that meets the requirements, and quantitatively transporting it to a spinning assembly by a metering pump; the PBO / PPA spinning solution is heated at 150-200°C. After being extruded through a spinneret and stretched through a 50-300 cm air gap layer, it enters a coagulation bath. Anti-aging agents have been added to the coagulation bath in advance. After passing through the coagulation bath, it is washed with 30-50°C warm water for about 50-300 meters, dried at 70-110°C, and then wound at a speed of 50-200 meters to obtain PBO raw yarn. If it continues to be heat treated at 550-650°C, high modulus PBO fiber will be obtained. However, the process is complicated, the operation is difficult, and the repeatability is low, making it difficult to apply to industrial production.
[0009] CN202010831346.1 discloses a method for preparing ultraviolet-resistant high-strength and high-modulus PBO fibers. Under the protection of inert gas, a PBO-AS fiber with axial tension is passed through a heat treatment channel to obtain the ultraviolet-resistant high-strength and high-modulus PBO fiber; the temperature of the heat treatment channel is 600-700°C, and the time for the PBO-AS fiber to pass through the heat treatment channel is no more than 10 minutes. By strictly controlling the heat treatment temperature and time, the tensile strength of the PBO fiber can be retained to the maximum extent, and at the same time, its tensile modulus is improved, which is of great benefit to the improvement of the ultraviolet resistance of the PBO fiber. However, this method improves the ultraviolet resistance of the fiber through high-temperature heat treatment, which has a certain effect on improving the ultraviolet aging resistance of the fiber, but the performance improvement is limited.
[0010] CN200810032210.3 provides a UV-resistant PBO fiber and a preparation method thereof, the preparation method comprising the following steps: heating and dissolving 4,6-diaminoresorcinol hydrochloride, terephthalic acid, phosphorus pentoxide and polyphosphoric acid, then reacting at 0.2-1.0MPa, 110-120°C for 5-7 hours, removing the pressure in the reactor, removing the HCl generated during the reaction, then adding a mixture of polyphosphoric acid and nano-TiO2, reacting at 140-150°C and 20-100Pa vacuum for 6-7 hours, and then preparing UV-resistant PBO fiber. The composite material obtained by in-situ polymerization can improve the UV resistance of PBO fiber and the flowability of the spinning solution, thereby increasing the winding speed to further improve the mechanical properties of the fiber. Since the mixed blend of polyphosphoric acid and nano-TiO2 is added in the polymerization stage, the method adds a UV absorber in the polymerization reactor, which may cause oxidation of the material and affect the product quality.
[0011] CN202110588383.9 discloses a PBO fiber sizing agent with UV aging resistance, PBO fiber and preparation method thereof, wherein a silane coupling agent with a mass percentage concentration of 0.1-5%, an epoxy resin with a mass percentage concentration of 0.1-5%, a light absorber with a mass percentage concentration of 1-10‰, and a light stabilizer with a mass fraction of 1-10‰ are mixed to obtain the PBO fiber sizing agent, and the sizing agent is applied to the PBO fiber in the sizing process to prepare the PBO fiber with UV aging resistance. The anti-ultraviolet aging performance of the fiber is improved by the surface coating method, without utilizing the large-scale and continuous preparation of PBO fiber.
[0012] Therefore, a simple and effective method for preparing high-strength and high-modulus PBO fibers that are resistant to UV aging is an urgent problem to be solved in the current PBO fiber research field. Summary of the invention
[0013] The purpose of the present invention is to propose a method for preparing PBO fiber resistant to ultraviolet aging. The prepolymerization process is intermittent and is used for intermittent preparation of prepolymer. The material is continuously transported from the storage kettle, and the anti-ultraviolet agent is added in the final polymerization stage. Since the viscosity of PBO spinning solution is large and it is easy to clog equipment and pipelines, the prepolymerization kettle, intermediate kettle, degassing kettle, twin-screw extruder and other equipment involved in the present invention should be compactly arranged in space arrangement, and the inner wall of the reactor and the inner wall of the pipeline involved should be polished to ensure the smoothness of the inner wall and reduce resistance. The spinning, coagulation, washing, oiling and drying steps involved in the invention are indispensable, and the densification process can be used as a supplement to obtain higher modulus fibers and further improve the anti-ultraviolet performance of the fibers. During the reaction process, the reaction time and reaction temperature should be strictly controlled to ensure the characteristic viscosity of the materials in each process and the process stability, so that the anti-ultraviolet aging PBO fiber can be obtained.
[0014] The technical solution of the present invention is achieved in this way:
[0015] The invention provides a high-strength and high-modulus PBO fiber resistant to ultraviolet aging, wherein the strength of the PBO fiber is 29.6-36.0 cN / dtex.
[0016] Preferably, the present invention further provides a high-strength and high-modulus PBO fiber that is resistant to ultraviolet aging, wherein the strength retention rate of the PBO fiber is ≥62.5%, preferably 62.5-90.5%.
[0017] In addition, the present invention also provides a method for preparing high-strength and high-modulus PBO fibers resistant to ultraviolet aging, comprising the following steps:
[0018] 1) Ingredients: Weigh terephthalic acid, 4,6-diaminoresorcinol hydrochloride, polyphosphoric acid, phosphorus pentoxide and antioxidant SnCl in a weight ratio of 9.5-9.9:11.9-12.3:52.2-57.6:16.5-18.0:0.06-20.05 to prepare PBO spinning solution; weigh polyphosphoric acid and anti-ultraviolet absorber UV326 in a weight ratio of 5.8-6.4:0.06-0.15 to prepare a blended solution;
[0019] 2) Prepolymerization: the PBO spinning solution prepared in step 1) is put into a prepolymerization reactor, nitrogen is introduced and emptied, stirring is started, the pressure in the reactor is maintained at <0.3Mpa, the temperature is maintained at 50-60°C, stirring is continued for 1-2h, then the temperature is raised to 90-100°C, stirring is continued for 1.5-2.0h, then the temperature is raised to 110-130°C, stirring is continued for 4-6h, to obtain a prepolymer;
[0020] 3) Material storage: reversely rotate the stirrer of the reactor in step 2), open the discharge valve at the bottom of the reactor, and the prepolymer enters the middle reactor through the twin-screw extruder, and keep the material discharged continuously. When the liquid level of the prepolymer material is about to reach 10%-20%, transfer the prepolymer in the reactor to the middle reactor, and keep the temperature of the middle reactor at 110-130°C;
[0021] 4) Degassing: The prepolymer in the intermediate reactor is pumped into the degassing reactor, the temperature is controlled at 130-140°C, and the pressure is controlled at -0.085 to -0.095MPa to obtain the degassing prepolymer;
[0022] 5) Pre-filtration: the defoamed prepolymer enters the pre-filter to obtain the filtered prepolymer;
[0023] 6) Final polymerization: the filtered prepolymer enters the final polymerization system, and the blended solution prepared in step 1) is pumped into the system under a slight vacuum state, the vacuum pressure is controlled at -0.045 to -0.085 MPa, the reaction temperature is controlled at 150-190° C., and the residence time is 30-45 min to obtain a final polymer;
[0024] 7) Spinning: The prepolymer of step 6) is pumped into a spinning assembly equipped with a filter screen, a distribution plate, and a spinneret, the temperature is controlled at 180-200°C, and the nozzle pressure is controlled at 4-10MPa to obtain
[0025] PBO fiber;
[0026] 8) Coagulation: The PBO fiber is then cooled in a coagulation bath at a temperature of 15-30°C to obtain cooled PBO fiber;
[0027] 9) Post-treatment: The cooled PBO fiber is first washed with water, then oiled, dried, and then collected to obtain PBO nascent fiber.
[0028] As a further improvement of the present invention, the intrinsic viscosity of the prepolymer in step 2) is 1.8-2.1 dL / g.
[0029] As a further improvement of the present invention, in step 2), a coaxial ribbon agitator is provided in the prepolymerization reactor, and a spiral discharge structure is provided at the bottom of the agitator.
[0030] As a further improvement of the present invention, a metering pump is provided at the bottom of the intermediate kettle in step 3).
[0031] As a further improvement of the present invention, the intrinsic viscosity of the prepolymer after degassing in step 4) is 8.0-17.8 dL / g, preferably 16.7-17.8 dL / g.
[0032] As a further improvement of the present invention, the degassing kettle in step 4) is equipped with an embedded vertical twin-screw extruder.
[0033] As a further improvement of the present invention, the degassing kettle in step 4) is a horizontal biaxial self-cleaning reactor, and preferably a vacuum pumping device is provided in the degassing kettle.
[0034] As a further improvement of the present invention, the pre-filter in step 5) is a plug-in filter.
[0035] As a further improvement of the present invention, the intrinsic viscosity of the final polymer in step 6) is
[0036] 31.8-32.6dL / g.
[0037] As a further improvement of the present invention, the spinneret in step 7) is provided with a filter screen and a distribution plate, the filter screen has a mesh size of 100-150 meshes, the spinneret has 60 to 120 holes, and the hole diameter is 0.25 to 0.30 mm.
[0038] As a further improvement of the present invention, after the PBO fibers are ejected from the spinneret in step 7), the PBO fibers enter a 30-50 cm air gap insulation layer.
[0039] As a further improvement of the present invention, the air gap layer in step 7) is electrically heated and kept warm, and the temperature is controlled at 40-80°C.
[0040] As a further improvement of the present invention, the coagulation bath in step 8) is a phosphoric acid aqueous solution, the phosphoric acid concentration is 10-20wt%, the coagulation bath temperature is 15-30°C, and the length is 1.5-2.0m.
[0041] As a further improvement of the present invention, the water washing in step 9) is carried out by upper spraying and lower immersion, and the temperature is controlled at 30-40°C.
[0042] As a further improvement of the present invention, the oiling in step 9) is performed by using an oil of PBO-001:PBO-002:PBO-003 in a weight ratio of 70:27:3 to 90:7:3 in an oil tank at 30-40°C.
[0043] As a further improvement of the present invention, the method further comprises a densification treatment, wherein the densification comprises: subjecting the PBO as-spun fibers to a densification treatment at ≥350° C. and then winding the fibers.
[0044] As a further improvement of the present invention, the densification treatment is carried out in a nitrogen atmosphere at 350-650°C.
[0045] The present invention has the following beneficial effects: The present invention aims at the conventional preparation process of PBO, solves the pain points and difficulties in the current preparation process of PBO by optimizing the process formula, reasonably setting the process flow, and adopting key equipment. The preparation method and the equipment used in the present invention need to cooperate with each other to perfectly realize the stable preparation of high-quality PBO fiber. By controlling the process conditions, the material transfer of each process is smooth, the material viscosity is moderate, and the fiber is thoroughly washed, and the anti-ultraviolet aging PBO fiber can be continuously and stably prepared.
[0046] 1) The present invention innovatively transforms the two steps of prepolymerization and final polymerization of the traditional PBO polymerization process into a semi-continuous process of prepolymerization, degassing and final polymerization through innovative design, and solves the problem of controlling the molecular weight growth of the prepolymer material in the intermittent reaction process through process control, which is beneficial to the unification of material indicators in each process and the stability of the process;
[0047] 2) The present invention uses UV326 as an anti-ultraviolet absorber. Since its color is similar to that of PBO fiber, it can be effectively blended in the PBO spinning solution without affecting the final color of the fiber.
[0048] 3) The present invention adds materials at one time, thus avoiding the operation steps of adding materials in batches and the problem that adding materials in the middle process may lead to oxidation in the air;
[0049] 4) The present invention adopts a pressurized degassing process to avoid the problem of uneven molar ratio caused by the material being sucked into the vacuum system under negative pressure;
[0050] 5) The present invention adopts a process of degassing and polymerizing at the same time, which avoids the disadvantage that the material is easily oxidized in the process of degassing first and then polymerizing;
[0051] 6) The present invention adopts a coaxial ribbon reactor as a prepolymerization reactor, which solves the problem of difficult mixing, dispersion and stirring of high-viscosity materials;
[0052] 7) The present invention provides a spiral material discharge structure at the lower part of the coaxial ribbon reactor, which is beneficial to the transfer of high-viscosity materials.
[0053] 8) The present invention cleverly arranges a twin-screw extruder at the bottom of the prepolymerization kettle, which can solve the problem of difficult transfer of prepolymer materials and ensure that the prepolymerization kettle materials are transferred cleanly and ready for use in the next batch of reactions;
[0054] 9) The present invention adopts a horizontal double-shaft devolatilization reactor as a degassing reactor, which solves the problem that HCl gas in PBO high-viscosity materials is difficult to remove;
[0055] 10) The degassing kettle used in the present invention is provided with an embedded vertical twin-screw extruder at the tail, which is conducive to the forced discharge of high-viscosity materials;
[0056] 11) The present invention sets a plug-in filter after the degassing kettle for pre-filtration, which can ensure that the material is fully filtered under low viscosity conditions, avoiding the problem of difficulty in filtering after the viscosity rises in the later stage;
[0057] 12) The present invention adopts a water washing system with upper spraying and lower immersion, which can fully wash the phosphoric acid of the PBO fiber and reduce the phosphorus content of the fiber;
[0058] 13) The oil formulation used in the present invention can significantly improve the fiber gloss, antistatic performance and anti-aging performance;
[0059] 14) The present invention adopts a high-temperature densification furnace to heat the fiber, which can significantly increase the modulus of the PBO fiber and further improve the fiber's anti-ultraviolet aging performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0060] Figure 1Schematic diagram of the preparation process of UV-resistant high-strength and high-modulus PBO fibers of Examples 1-4. DETAILED DESCRIPTION
[0061] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0062] Unless otherwise defined, all technical and scientific terms used herein have the same meanings as commonly understood by those of ordinary skill in the art to which the invention belongs. Although any methods and materials similar or equivalent to those described herein can be used to implement or test the present invention, preferred methods and materials are described herein. For purposes of the present invention, the following terms are defined below.
[0063] PBO spinning solution
[0064] The PBO spinning solution of the present invention is prepared from the following raw materials by weight: 9.5-9.9% of terephthalic acid, 11.9-12.3% of 4,6-diaminoresorcinol hydrochloride, 52.2-57.6% of polyphosphoric acid, 16.5-18.0% of phosphorus pentoxide, 0.05-0.06% of antioxidant, and 26% of ultraviolet absorber UV3.
[0065] UV absorber configuration
[0066] The ultraviolet absorber of the present invention is configured by dividing polyphosphoric acid into two parts according to a weight ratio of 9:1, wherein 9 parts are used for polymerization reaction and 1 part is used for the configuration of the ultraviolet absorber; that is, polyphosphoric acid and UV326 with a weight ratio of 5.8-6.4:0.06-0.15 are blended and stirred evenly, and the polyphosphoric acid needs to be heated to 60-80°C before blending to obtain a PPA-UV326 blended solution.
[0067] Pre-polymerization
[0068] The prepolymerization of the present invention is to feed the PBO spinning solution raw material into the prepolymerization reactor at one time. After the feeding is completed, nitrogen is introduced and emptied, the pressure in the reactor is maintained at 0.1-0.3MPa, the prepolymerization stirrer is turned on, the temperature is controlled within the range of 50-60°C, stirring is continued for 1-2h, then the temperature is increased to 90-100°C, stirring is continued for 1.5-2.0h, then the temperature is increased to 110-130°C, stirring is continued for 4-6h, HCl gas will be generated during the stirring period, when the pressure in the reactor rises to 0.2-0.4MPa, the pressure is released to 0.1-0.3MPa through the pressure relief device, and this operation is repeated according to the total amount of feeding until the pressure no longer rises.
[0069] Storage
[0070] The material storage of the present invention is that after the prepolymerization reaction is completed, the stirrer of the reactor is rotated in the opposite direction, and the bottom discharge valve is opened, and the material enters the middle reactor through the twin-screw extruder; the middle reactor keeps discharging the material continuously, and when the material liquid level is about to reach 10%-20%, the material in the prepolymerization reactor is transferred to the middle reactor, and the temperature of the middle reactor is maintained at 110-130°C.
[0071] Defoaming
[0072] The degassing process of the present invention is to pump the prepolymer material into the degassing kettle by a metering pump at the bottom of the middle kettle, the temperature is controlled at 130-140°C, and the reaction pressure is controlled at -0.085 to -0.095MPa.
[0073] Pre-filtration
[0074] The pre-filtration of the present invention is that the pre-polymerized material enters the pre-filter after being pressurized by a gear pump, and most of the impurities in the material can be filtered out.
[0075] Final Reunion
[0076] The final polymerization of the present invention is to feed the filtered prepolymer material into a twin-screw extruder, and at the same time pump PPA-UV326 into the twin-screw extruder through a side feed port, blend with the polymerization liquid, further polymerize and remove trace HCl under a slight vacuum state, the vacuum pressure is controlled at -0.045 to -0.085 MPa, the reaction temperature is controlled at 150-190° C., and the residence time is 30-45 min.
[0077] Spinning
[0078] The spinning of the present invention is that the final polymer is pumped into a spinning assembly provided with a filter screen, a distribution plate and a spinneret through a metering pump, the spinneret is provided with a filter screen and a distribution plate, further filtering trace impurities and distributing the final polymer material to the spinneret, the filter screen has 100-150 meshes, the spinneret has 60-120 holes, the hole diameter is 0.25-0.30mm, the assembly temperature is controlled at 180-200°C, and the nozzle pressure is controlled at 4-10MPa. The PBO fiber ejected from the spinneret enters a section, for example, 30-50cm of air gap insulation layer, the temperature of which is 40-80°C.
[0079] solidification
[0080] The coagulation of the present invention is that the spinning fiber enters the coagulation bath device, the coagulation bath is a phosphoric acid aqueous solution, the phosphoric acid concentration is 10-20% by mass, the coagulation bath temperature is 15-30°C, the length is 1.5-2.0m, the fiber is fully cooled in the coagulation bath, and the fiber surface defects are improved.
[0081] Post-processing
[0082] The post-treatment of the present invention is that the fiber first enters a water washing device to remove phosphoric acid in the fiber, the phosphoric acid after water washing enters an oiling tank to oil the fiber, and after the oiling is completed, the fiber enters a dryer, and the dried fiber is collected by a winder to obtain golden PBO-AS nascent fiber.
[0083] Densification
[0084] The densification step described in the present invention can be used as a further supplement to obtain UV-resistant fibers. The above-mentioned primary fibers enter a high-temperature densification furnace. After the fibers are heated in the densification furnace, PBO-HM fibers with higher modulus can be obtained. At the same time, the UV resistance of the fibers is further improved, and the fiber color is brown.
[0085] As used herein, the term "about" refers to an amount, level, value, dimension, size, or amount that differs by up to 30%, 20%, or 10% compared to the amount, level, value, dimension, size, or amount of a reference product. Percentages used herein, unless otherwise indicated, are by weight.
[0086] Throughout the specification and claims, unless otherwise required, the following words "comprise" and variations "comprising" and "including" will be understood to imply the inclusion of a stated integer or step, or a group of integers or steps, but not the exclusion of any other integer or step, or other group of integers or steps.
[0087] Experimental Materials:
[0088]
[0089]
[0090] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The experimental methods in the following examples without specifying specific conditions are carried out according to conventional methods and conditions, or selected according to the product specifications.
[0091] Embodiment 1:
[0092] Ingredients: Weigh 5.45kgPTA, 6.55kgDAR, 32.9kgPPA, 9.65kgP2O5, 32.5g SnCl2, and 35gUV326 respectively and set aside;
[0093] The weighed 32.9 kg PPA was divided into two parts, 29.6 kg and 3.3 kg, of which 29.6 kg PPA was used for polymerization reaction, and the other 3.3 kg PPA was heated to 80° C., blended with the weighed 35 g UV326, and stirred evenly to obtain a PPA-UV326 blend solution.
[0094] Prepolymerization: Put the weighed polymerization materials into the prepolymerization kettle at one time. After the feeding is completed, nitrogen is introduced and emptied several times to maintain the pressure in the kettle at 0.30MPa. The prepolymerization agitator is turned on, and the temperature is controlled within the range of 60℃. Stirring is continued for 2h, then the temperature is raised to 100℃, stirring is continued for 1.5h, then the temperature is raised to 120℃, stirring is continued for 5h, during which HCl gas will be generated. When the pressure in the reactor rises to 0.35MPa, the pressure is released to 0.25MPa through the pressure relief device, then the temperature is raised to 130℃, stirring is continued for 2h, and the vacuum state is maintained to control the reaction pressure to -0.090MPa. After the reaction is completed, the characteristic viscosity of the prepolymer material is sampled and analyzed to be 2.1dL / g.
[0095] Material storage: After the prepolymerization reaction is completed, the agitator of the prepolymerization reactor is rotated in the opposite direction, and the bottom discharge valve is opened, and the material enters the intermediate reactor through the twin-screw extruder. The intermediate reactor keeps discharging the material continuously. When the material liquid level is about to reach 20%, the material in the prepolymerization reactor is transferred to the intermediate reactor, and the temperature of the intermediate reactor is maintained at 130°C.
[0096] Degassing: The metering pump at the bottom of the middle reactor pumps the prepolymer material into the degassing reactor. The temperature of the degassing reactor is controlled at 140°C, the reaction pressure is controlled at -0.090MPa, and the material residence time is controlled at 4.0h. After the degassing is completed, the material intrinsic viscosity is measured to be 17.8dL / g.
[0097] Pre-filtration: The defoamed prepolymer enters the pre-filter to obtain the filtered prepolymer;
[0098] Final polymerization: The filtered material is fed into the final polymerization system, and the PPA-UV326 blend solution is pumped into the system through the side feeding port of the twin-screw extruder. The material residence time in the extruder is controlled to be 45 minutes, and the temperature is set according to the gradient of 150°C, 160°C, 170°C, 175°C, 180°C, 185°C, and 190°C. The pressure is controlled at -0.085MPa. After the final polymerization, the material characteristic viscosity is tested by sampling and the result is 32.6dL / g.
[0099] Spinning: The material is pumped into the spinning assembly equipped with a filter screen, a distribution plate, and a spinneret through a metering pump. The spinneret is equipped with a filter screen and a distribution plate to further filter trace impurities and distribute the final polymer material to the spinneret. The filter screen has a mesh size of 100-150, the spinneret has 60-120 holes, and the hole diameter is 0.25-0.30mm. The assembly temperature is controlled at 180-200℃, and the nozzle pressure is controlled at 4-10MPa. The PBO fiber ejected from the spinneret enters a 30-50cm air gap insulation layer with a temperature of 40-80℃.
[0100] Coagulation: The fiber enters a coagulation bath with a concentration of 20%, a temperature of 30°C and a length of 1.5 m for sufficient cooling.
[0101] Post-treatment: The coagulated fiber enters the post-treatment device, the washing water temperature is controlled at 40°C, the oil agent ratio is PBO-001:PBO-002:PBO-003=80:17:3, the oil agent temperature is controlled at 40°C, and the fiber is wound and collected after drying.
[0102] Densification: Densification treatment of the spun fibers: The spun fibers are placed in a high-temperature densification furnace, the temperature of which is controlled at 600°C, and are wound and collected after high-temperature heat treatment for later use.
[0103] Embodiment 2:
[0104] Ingredients: Weigh 5.45kgPTA, 6.55kgDAR, 33.0kgPPA, 9.55kgP2O5, 32.5g SnCl2, and 50gUV326 respectively and set aside; divide the weighed 33.0kg PPA into two parts, 30.0kg and 3.0kg, of which 30.0kgPPA is used for polymerization reaction, and the other 3.0kgPPA is heated to 80°C, blended with the weighed 50g UV326, and stirred evenly to obtain a PPA-UV326 blended solution.
[0105] Prepolymerization: Add the weighed polymerization materials into the prepolymerization kettle at one time. After the feeding is completed, nitrogen is introduced and emptied several times to maintain the pressure in the kettle at 0.30MPa. The prepolymerization agitator is turned on, and the temperature is controlled within the range of 60℃. Stirring is continued for 2h, then the temperature is raised to 100℃, stirring is continued for 1.5h, then the temperature is raised to 120℃, stirring is continued for 5h, during which HCl gas will be generated. When the pressure in the reactor rises to 0.35MPa, the pressure is released to 0.25MPa through the pressure relief device, then the temperature is raised to 130℃, stirring is continued for 2h, and the vacuum state is maintained to control the reaction pressure to -0.090MPa. After the reaction is completed, the characteristic viscosity of the prepolymer material is sampled and analyzed to be 2.0dL / g.
[0106] Material storage: After the prepolymerization reaction is completed, the agitator of the prepolymerization reactor is rotated in the opposite direction, and the bottom discharge valve is opened, and the material enters the intermediate reactor through the twin-screw extruder. The intermediate reactor keeps discharging the material continuously. When the material liquid level is about to reach 20%, the material in the prepolymerization reactor is transferred to the intermediate reactor, and the temperature of the intermediate reactor is maintained at 130°C.
[0107] Degassing: The prepolymer material is pumped into the degassing kettle by the metering pump at the bottom of the middle kettle. The temperature of the degassing kettle is controlled at 140°C, the reaction pressure is controlled at -0.090MPa, and the material residence time is controlled at 4.0h. After the degassing is completed, the material intrinsic viscosity is measured to be 17.4dL / g.
[0108] Pre-filtration: The defoamed prepolymer enters the pre-filter to obtain the filtered prepolymer;
[0109] Final polymerization: The filtered material is fed into the final polymerization system. At the same time, PPA-UV326 is pumped into the system through the side feeding port of the twin-screw extruder. The material residence time in the extruder is controlled to be 45 minutes. The temperature is set according to the gradient of 150℃, 160℃, 170℃, 175℃, 180℃, 185℃, and 190℃. The pressure is controlled at -0.085MPa. After the final polymerization, the material characteristic viscosity is tested by sampling and the result is 32.3dL / g.
[0110] Spinning: The material is pumped into the spinning assembly equipped with a filter screen, a distribution plate, and a spinneret through a metering pump. The spinneret is equipped with a filter screen and a distribution plate to further filter trace impurities and distribute the final polymer material to the spinneret. The filter screen has a mesh size of 100-150, the spinneret has 60-120 holes, and the hole diameter is 0.25-0.30mm. The assembly temperature is controlled at 180-200℃, and the nozzle pressure is controlled at 4-10MPa. The PBO fiber ejected from the spinneret enters a 30-50cm air gap insulation layer with a temperature of 40-80℃.
[0111] Coagulation: The fiber enters a coagulation bath with a concentration of 20%, a temperature of 30°C and a length of 1.5 m for sufficient cooling.
[0112] Post-treatment: The coagulated fiber enters the post-treatment device, the washing water temperature is controlled at 40°C, the oil agent ratio is PBO-001:PBO-002:PBO-003=80:17:3, the oil agent temperature is controlled at 40°C, and the fiber is wound and collected after drying.
[0113] Densification: Densification treatment of the spun fibers: The spun fibers are placed in a high-temperature densification furnace, the temperature of which is controlled at 600°C, and are wound and collected after high-temperature heat treatment for later use.
[0114] Embodiment 3:
[0115] Ingredients: Weigh 5.40kgPTA, 6.66kgDAR, 33.5kgPPA, 9.55kgP2O5, 30.0g SnCl2, and 65gUV326 respectively and set aside; divide the weighed 33.5kg PPA into two parts, 30.0kg and 3.5kg, of which 30.0kgPPA is used for polymerization reaction, and the other 3.5kgPPA is heated to 80℃, blended with the weighed 65g UV326, and stirred evenly to obtain a PPA-UV326 blended solution.
[0116] Prepolymerization: Add the weighed polymerization materials into the prepolymerization kettle at one time. After the feeding is completed, nitrogen is introduced and emptied several times to maintain the pressure in the kettle at 0.30MPa. The prepolymerization agitator is turned on, and the temperature is controlled within the range of 60℃. Stirring is continued for 2h, then the temperature is raised to 100℃, stirring is continued for 1.5h, then the temperature is raised to 120℃, stirring is continued for 5h, during which HCl gas will be generated. When the pressure in the reactor rises to 0.35MPa, the pressure is released to 0.25MPa through the pressure relief device, then the temperature is raised to 130℃, stirring is continued for 2h, and the vacuum state is maintained to control the reaction pressure to -0.090MPa. After the reaction is completed, the characteristic viscosity of the prepolymer material is sampled and analyzed to be 1.8dL / g.
[0117] Material storage: After the prepolymerization reaction is completed, the agitator of the prepolymerization reactor is rotated in the opposite direction, and the bottom discharge valve is opened, and the material enters the intermediate reactor through the twin-screw extruder. The intermediate reactor keeps discharging the material continuously. When the material liquid level is about to reach 20%, the material in the prepolymerization reactor is transferred to the intermediate reactor, and the temperature of the intermediate reactor is maintained at 130°C.
[0118] Degassing: The prepolymer material is pumped into the degassing kettle by the metering pump at the bottom of the middle kettle. The temperature of the degassing kettle is controlled at 140°C, the reaction pressure is controlled at -0.090MPa, and the material residence time is controlled at 4.0h. After the degassing is completed, the material intrinsic viscosity is measured to be 16.7dL / g.
[0119] Pre-filtration: The defoamed prepolymer enters the pre-filter to obtain the filtered prepolymer;
[0120] Final polymerization: The filtered material is fed into the final polymerization system. At the same time, PPA-UV326 is pumped into the system through the side feeding port of the twin-screw extruder. The material residence time in the extruder is controlled to be 45 minutes. The temperature is set according to the gradient of 150℃, 160℃, 170℃, 175℃, 180℃, 185℃, and 190℃. The pressure is controlled at -0.085MPa. After the final polymerization, the material characteristic viscosity is tested by sampling and the result is 31.8dL / g.
[0121] Spinning: The material is pumped into the spinning assembly equipped with a filter screen, a distribution plate, and a spinneret through a metering pump. The spinneret is equipped with a filter screen and a distribution plate to further filter trace impurities and distribute the final polymer material to the spinneret. The filter screen has a mesh size of 100-150, the spinneret has 60-120 holes, and the hole diameter is 0.25-0.30mm. The assembly temperature is controlled at 180-200℃, and the nozzle pressure is controlled at 4-10MPa. The PBO fiber ejected from the spinneret enters a 30-50cm air gap insulation layer with a temperature of 40-80℃.
[0122] Coagulation: The fiber enters a coagulation bath with a concentration of 20%, a temperature of 30°C and a length of 1.5 m for sufficient cooling.
[0123] Post-treatment: The coagulated fiber enters the post-treatment device, the washing water temperature is controlled at 40°C, the oil agent ratio is PBO-001:PBO-002:PBO-003=80:17:3, the oil agent temperature is controlled at 40°C, and the fiber is wound and collected after drying.
[0124] Densification: Densification treatment of the spun fibers: The spun fibers are placed in a high-temperature densification furnace, the temperature of which is controlled at 600°C, and are wound and collected after high-temperature heat treatment for later use.
[0125] Embodiment 4:
[0126] Ingredients: Weigh 5.40kgPTA, 6.66kgDAR, 33.2kgPPA, 9.60kgP2O5, 30.0g SnCl2, and 80gUV326 respectively and set aside; divide the weighed 33.2kg PPA into two parts, 30.0kg and 3.2kg, of which 30.0kgPPA is used for polymerization reaction, and the other 3.2kgPPA is heated to 80℃, blended with the weighed 80g UV326, and stirred evenly to obtain a PPA-UV326 blended solution.
[0127] Prepolymerization: Add the weighed polymerization materials into the prepolymerization kettle at one time. After the feeding is completed, nitrogen is introduced and emptied several times to maintain the pressure in the kettle at 0.30MPa. The prepolymerization agitator is turned on, and the temperature is controlled within the range of 60℃. Stirring is continued for 2h, then the temperature is raised to 100℃, stirring is continued for 1.5h, then the temperature is raised to 120℃, stirring is continued for 5h, during which HCl gas will be generated. When the pressure in the reactor rises to 0.35MPa, the pressure is released to 0.25MPa through the pressure relief device, then the temperature is raised to 130℃, stirring is continued for 2h, and the vacuum state is maintained to control the reaction pressure to -0.090MPa. After the reaction is completed, the characteristic viscosity of the prepolymer material is sampled and analyzed to be 2.0dL / g.
[0128] Material storage: After the prepolymerization reaction is completed, the agitator of the prepolymerization reactor is rotated in the opposite direction, and the bottom discharge valve is opened, and the material enters the intermediate reactor through the twin-screw extruder. The intermediate reactor keeps discharging the material continuously. When the material liquid level is about to reach 20%, the material in the prepolymerization reactor is transferred to the intermediate reactor, and the temperature of the intermediate reactor is maintained at 130°C.
[0129] Degassing: The prepolymer material is pumped into the degassing kettle by the metering pump at the bottom of the middle kettle. The temperature of the degassing kettle is controlled at 140°C, the reaction pressure is controlled at -0.090MPa, and the material residence time is controlled at 4.0h. After the degassing is completed, the material intrinsic viscosity is measured to be 17.2dL / g.
[0130] Pre-filtration: The defoamed prepolymer enters the pre-filter to obtain the filtered prepolymer;
[0131] Final polymerization: The filtered material is fed into the final polymerization system. At the same time, PPA-UV326 is pumped into the system through the side feeding port of the twin-screw extruder. The material residence time in the extruder is controlled to be 45 minutes. The temperature is set according to the gradient of 150℃, 160℃, 170℃, 175℃, 180℃, 185℃, and 190℃. The pressure is controlled at -0.085MPa. After the final polymerization, the material characteristic viscosity is tested by sampling and the result is 32.0dL / g.
[0132] Spinning: The material is pumped into the spinning assembly equipped with a filter screen, a distribution plate, and a spinneret through a metering pump. The spinneret is equipped with a filter screen and a distribution plate to further filter trace impurities and distribute the final polymer material to the spinneret. The filter screen has a mesh size of 100-150, the spinneret has 60-120 holes, and the hole diameter is 0.25-0.30mm. The assembly temperature is controlled at 180-200℃, and the nozzle pressure is controlled at 4-10MPa. The PBO fiber ejected from the spinneret enters a 30-50cm air gap insulation layer with a temperature of 40-80℃.
[0133] Coagulation: The fiber enters a coagulation bath with a concentration of 20%, a temperature of 30°C and a length of 1.5 m for sufficient cooling.
[0134] Post-treatment: The coagulated fiber enters the post-treatment device, the washing water temperature is controlled at 40°C, the oil agent ratio is PBO-001:PBO-002:PBO-003=80:17:3, the oil agent temperature is controlled at 40°C, and the fiber is wound and collected after drying.
[0135] Densification: Densification treatment of the spun fibers: The spun fibers are placed in a high-temperature densification furnace, the temperature of which is controlled at 600°C, and are wound and collected after high-temperature heat treatment for later use.
[0136] Comparative Example 1:
[0137] Ingredients: Weigh 5.45kgPTA, 6.55kgDAR, 32.9kgPPA, 9.65kgP2O5, and 32.5g SnCl 2 respectively and set aside.
[0138] Prepolymerization: Put the weighed polymerization materials into the prepolymerization kettle at one time. After the feeding is completed, nitrogen is introduced and emptied several times to maintain the pressure in the kettle at 0.30MPa. The prepolymerization agitator is turned on, and the temperature is controlled within the range of 60℃. Stirring is continued for 2h, then the temperature is raised to 100℃, stirring is continued for 1.5h, then the temperature is raised to 120℃, stirring is continued for 5h, during which HCl gas will be generated. When the pressure in the reactor rises to 0.35MPa, the pressure is released to 0.25MPa through the pressure relief device, then the temperature is raised to 130℃, stirring is continued for 2h, and the vacuum state is maintained to control the reaction pressure to -0.090MPa. After the reaction is completed, the characteristic viscosity of the prepolymer material is sampled and analyzed to be 2.3dL / g.
[0139] Material storage: After the prepolymerization reaction is completed, the agitator of the prepolymerization reactor is rotated in the opposite direction, and the bottom discharge valve is opened, and the material enters the intermediate reactor through the twin-screw extruder. The intermediate reactor keeps discharging the material continuously. When the material liquid level is about to reach 20%, the material in the prepolymerization reactor is transferred to the intermediate reactor, and the temperature of the intermediate reactor is maintained at 130°C.
[0140] Degassing: The prepolymer material is pumped into the degassing kettle by the metering pump at the bottom of the middle kettle. The temperature of the degassing kettle is controlled at 140°C, the reaction pressure is controlled at -0.090MPa, and the material residence time is controlled at 4.0h. After the degassing is completed, the material intrinsic viscosity is measured to be 18.0dL / g.
[0141] Pre-filtration: The defoamed prepolymer enters the pre-filter to obtain the filtered prepolymer;
[0142] Final polymerization: the filtered material is sent to the final polymerization system. The residence time of the material in the extruder is controlled to be 45 minutes. The temperature is set according to the gradient of 150℃, 160℃, 170℃, 175℃, 180℃, 185℃, and 190℃. The pressure is controlled at -0.085MPa. After the final polymerization, the material characteristic viscosity is tested by sampling and the result is 32.8dL / g.
[0143] Spinning: The material is pumped into the spinning assembly equipped with a filter screen, a distribution plate, and a spinneret through a metering pump. The spinneret is equipped with a filter screen and a distribution plate to further filter trace impurities and distribute the final polymer material to the spinneret. The filter screen has a mesh size of 100-150, the spinneret has 60-120 holes, and the hole diameter is 0.25-0.30mm. The assembly temperature is controlled at 180-200℃, and the nozzle pressure is controlled at 4-10MPa. The PBO fiber ejected from the spinneret enters a 30-50cm air gap insulation layer with a temperature of 40-80℃.
[0144] Coagulation: The fiber enters a coagulation bath with a concentration of 20%, a temperature of 30°C and a length of 1.5 m for sufficient cooling.
[0145] Post-treatment: The coagulated fiber enters the post-treatment device, the washing water temperature is controlled at 40°C, the oil agent ratio is PBO-001:PBO-002:PBO-003=80:17:3, the oil agent temperature is controlled at 40°C, and the fiber is wound and collected after drying.
[0146] Densification: Densification treatment of the spun fibers: The spun fibers are placed in a high-temperature densification furnace, the temperature of which is controlled at 600°C, and are wound and collected after high-temperature heat treatment for later use.
[0147] Test Example 1:
[0148] Test samples: PBO fibers prepared in Examples 1-4 and Comparative Example 1
[0149] The PBO fibers prepared in Examples 1-4 of the present invention and Comparative Example 1 were irradiated with ultraviolet light for 100 hours, and performance tests were performed. The results are shown in Table 1.
[0150] The equipment used for the UV aging test was a xenon lamp weathering test chamber, model SN-500, produced by Shanghai Linpin Technology Co., Ltd. The experimental conditions were irradiation intensity of 1100W / m 2 , temperature 55℃, relative humidity 65%. No special treatment is required for the samples.
[0151] The fibers prepared in Examples 1-4 were subjected to strength tests before and after being irradiated with UV light for 100 hours.
[0152] The strength test was conducted by online testing using the XQ-1 fiber tensile tester and the XD-1 vibration fineness tester, produced by Shanghai Xinxian Instrument Co., Ltd. The fixture specifications used in the test were: 0.33cN, clamping distance: 20mm, and tensile speed 10mm / min. During the test, 30 single filament fibers from each group of samples were extracted for testing, and the average value was taken to obtain the fiber line strength.
[0153] Strength retention rate = 100-hour strength / 0-hour strength*100%.
[0154] Table 1
[0155]
[0156] Through the UV aging test, with the increase of the added amount of UV resistant agent UV326 in the embodiment, the fiber strength retention rate gradually increased, which shows that the UV resistant agent UV326 can effectively improve the UV resistance of the fiber.
[0157] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-strength and high-modulus PBO fiber resistant to ultraviolet aging, characterized in that: The PBO fiber strength is 29.6-36.0 cN / dtex.
2. The ultraviolet aging resistant high-strength and high-modulus PBO fiber according to claim 1, characterized in that: The strength retention rate of the PBO fiber is ≥62.5%, preferably 62.5-90.5%.
3. A method for preparing the ultraviolet aging resistant high-strength and high-modulus PBO fiber as claimed in claim 1, comprising the following steps: 1) Ingredients: Weigh terephthalic acid, 4,6-diaminoresorcinol hydrochloride, polyphosphoric acid, phosphorus pentoxide and antioxidant SnCl in a weight ratio of 9.5-9.9:11.9-12.3:52.2-57.6:16.5-18.0:0.06-20.05 to prepare PBO spinning solution; weigh polyphosphoric acid and anti-ultraviolet absorber UV326 in a weight ratio of 5.8-6.4:0.06-0.15 to prepare a blended solution; 2) Prepolymerization: The PBO spinning solution prepared in step 1) is put into a prepolymerization reactor, nitrogen is introduced and emptied, stirring is started, the pressure in the reactor is maintained at <0.3Mpa, the temperature is maintained at 50-60°C, stirring is continued for 1-2h, then the temperature is raised to 90-100°C, stirring is continued for 1.5-2.0h, and then the temperature is raised to 110-130°C, continue stirring for 4-6 hours to obtain a prepolymer; 3) Material storage: reversely rotate the stirrer of the reactor in step 2), open the discharge valve at the bottom of the reactor, and the prepolymer enters the middle reactor through the twin-screw extruder, and keep the material discharged continuously. When the liquid level of the prepolymer material is about to reach 10%-20%, transfer the prepolymer in the reactor to the middle reactor, and keep the temperature of the middle reactor at 110-130°C; 4) Degassing: The prepolymer in the intermediate reactor is pumped into the degassing reactor, the temperature is controlled at 130-140°C, and the pressure is controlled at -0.085 to -0.095MPa to obtain the degassing prepolymer; 5) Pre-filtration: the defoamed prepolymer enters the pre-filter to obtain the filtered prepolymer; 6) Final polymerization: the filtered prepolymer enters the final polymerization system, and the blended solution prepared in step 1) is pumped into the system under a slight vacuum state, the vacuum pressure is controlled at -0.045 to -0.085 MPa, the reaction temperature is controlled at 150-190° C., and the residence time is 30-45 min to obtain a final polymer; 7) Spinning: The final polymer of step 6) is pumped into a spinning assembly equipped with a filter screen, a distribution plate, and a spinneret, the temperature is controlled at 180-200° C., and the nozzle pressure is controlled at 4-10 MPa to obtain PBO fibers; 8) Coagulation: The PBO fiber is then cooled in a coagulation bath at a temperature of 15-30°C to obtain cooled PBO fiber; 9) Post-treatment: The cooled PBO fiber is first washed with water, then oiled, dried, and then collected to obtain PBO nascent fiber.
4. The method according to claim 3, characterized in that The intrinsic viscosity of the prepolymer in step 2) is 1.8-2.1 dL / g.
5. The method according to claim 3, characterized in that In step 2), a coaxial ribbon agitator is arranged in the prepolymerization reactor, and a spiral discharging structure is arranged at the bottom of the agitator.
6. The method according to claim 3, characterized in that In step 3), a metering pump is provided at the bottom of the intermediate kettle.
7. The method according to claim 3, characterized in that The intrinsic viscosity of the prepolymer after degassing in step 4) is 8.0-17.8 dL / g, preferably 16.7-17.8 dL / g.
8. The method according to claim 3, characterized in that The degassing kettle in step 4) is equipped with an embedded vertical twin-screw extruder.
9. The method according to claim 8, characterized in that The degassing kettle in step 4) is a horizontal biaxial self-cleaning reactor, and preferably a vacuum pumping device is provided in the degassing kettle.
10. The method according to claim 3, characterized in that The pre-filter in step 5) is a plug-in filter.
11. The method according to claim 3, characterized in that The intrinsic viscosity of the final polymer in step 6) is 31.8-32.6 dL / g.
12. The method according to claim 3, characterized in that In step 7), the spinneret is provided with a filter screen and a distribution plate, the filter screen has a mesh size of 100-150 meshes, the spinneret has 60-120 holes, and the hole diameter is 0.25-0.30 mm.
13. The method according to claim 3, characterized in that After the PBO fibers are ejected from the spinneret in step 7), the PBO fibers enter a 30-50 cm air gap insulation layer.
14. The method according to claim 13, characterized in that In step 7), the air gap layer is electrically heated and kept warm, and the temperature is controlled at 40-80°C.
15. The method according to claim 3, characterized in that In step 8), the coagulation bath is a phosphoric acid aqueous solution with a phosphoric acid concentration of 10-20 wt %, a coagulation bath temperature of 15-30° C., and a length of 1.5-2.0m。 16. The method according to claim 3, characterized in that The water washing in step 9) is carried out by spraying from above and dipping from below, and the temperature is controlled at 30-40°C.
17. The method according to claim 3, characterized in that The oiling in step 9) is performed by using an oil of PBO-001:PBO-002:PBO-003 in a weight ratio of 70:27:3 to 90:7:3 in an oil tank at 30-40°C.
18. The method according to claim 3, characterized in that The method further comprises a densification treatment, wherein the densification comprises: subjecting the PBO spun fibers to a densification treatment at ≥350° C. and then winding the fibers for collection.
19. The method according to claim 18, characterized in that The densification treatment is performed in a nitrogen atmosphere at 350-650°C.
Citation Information
Patent Citations
Ultraviolet resisting PBO fibre and preparing method thereof
CN101215732B
Preparation method of anti-ultraviolet aging polyphenylene benzodioxazole fiber
CN101906677B
A method for resisting UV aging of poly(p-phenylenebenzodioxazole) fibers
CN102277726A
Ultraviolet-resistant type high-strength and high-modulus PBO fibers, and preparation method thereof
CN111926438A
Sizing agent for PBO fiber with ultraviolet aging resistance, PBO fiber and preparation method of sizing agent
CN113293614A